Aktivitas Antiproliferasi Ekstrak Etanol Biji Kopi Hijau Robusta Lampung pada Sel Lestari Tumor Anjing - Sasmita, Farra; Wientarsih, Ietje; Prasetyo, Bayu Febram; Priosoeryanto, Bambang Pontjo (Jurnal Veteriner, 2021)
This study aim at determining the activity of ethanol extract of Robusta green coffee beans as an antiproliferation agent in MCA-B1, MCM-B2, and Vero normal cell lines as a control. Ethanol extract of Robusta green coffee beans was obtained by maceration method, bioactive compounds in the extract were tested by phytochemical screening methods, testing levels of antioxidants were tested by 2,2-diphenyl-1-picrylhydrazyl (DPPH) method, cytotoxicity effects (LC50) were tested by the method Brine Shrimp Lethallity Test (BSLT) and antiproliferation activity were carried out by counting the number of cells after being tested with several extract concentrations namely 100, 250, 400, 550, 700 and 850 ppm and doxorubicin as a positive control with a concentration of 100 ppm. The results showed that the ethanol extract of Robusta green coffee beans contained flavonoids and tannins, had very strong antioxidant levels with IC50 values   of 40.9923 ppm, cytotoxicity effects obtained LC50 values   of 430.64 ppm, and the highest antiproliferation activity was achieved at a concentration of 850 ppm at 69.58 % in MCM-B2 tumor cells, 60.46% in MCA-B1 tumor cells, and 14.2% in Vero normal cells. Based on the results, the ethanol extract of Robusta Lampung green coffee beans has antiproliferation activity on the test tumor cells and is relatively non-toxic to normal cells.